Efeito das bactérias dos nódulos radiculares sobre o rendimento da cultura da lentilha - Vieira, Clibas (Revista Ceres, 2024)
Lentils, as a crop, are unknown in the state of Minas Gerais, Brazil. With the objective of studying the possibility of lentil cultivation in the locality of Vigosa, several varieties were introduced. The variety Comercial was used to determine the effect of inoculation with rootnodule bacteria onyield. Soil,from an areapreviously planted with common peas, was usedasthe inoculant. Onunlimed plots inoculated plants yielded 23% more seed weight and 16% more dry plant material than the unlimed, uninoculated check plots. On inoculated plots, limed at the rate of 3,000 kg/ha, the yieldincreases were 37% and 38%, respectively, over the unlimed ,uninoculated check plots.